Danoprevir for the Treatment of Hepatitis C Virus Infection: Design, Development, and Place in Therapy - Miao M; Jing X; De Clercq E; Li G (Dove Medical Press, 2020)
Miao Miao,1 Xixi Jing,1 Erik De Clercq,2 Guangdi Li1 1Hunan Provincial Key Laboratory of Clinical Epidemiology, Xiangya School of Public Health, Central South University, Changsha 410078, People’s Republic of China; 2Department of Microbiology, Immunology and Transplantation, Rega Institute for Medical Research, KU Leuven, Leuven 3000, BelgiumCorrespondence: Guangdi Li Email liguangdi.research@gmail.comAbstract: On June 8, 2018, an NS3/4A protease inhibitor called danoprevir was approved in China to treat the infections of HCV genotype (GT) 1b – the most common HCV genotype worldwide. Based on phase 2 and 3 clinical trials, the 12-week regimen of ritonavir-boosted danoprevir (danoprevir/r) plus peginterferon alpha-2a and ribavirin offered 97.1% (200/206) of sustained virologic response at post-treatment week 12 (SVR12) in treatment-naïve non-cirrhotic patients infected with HCV genotype 1b. Adverse events such as anemia, fatigue, fever, and headache were associated with the inclusion of peginterferon alpha-2a and ribavirin in the danoprevir-based regimen. Moreover, drug resistance to danoprevir could be traced to amino acid substitutions (Q80K/R, R155K, D168A/E/H/N/T/V) near the drug-binding pocket of HCV NS3 protease. Despite its approval, the clinical use of danoprevir is currently limited to its combination with peginterferon alpha-2a and ribavirin, thereby driving its development towards interferon-free, ribavirin-free regimens with improved tolerability and adherence. In the foreseeable future, pan-genotypic direct-acting antivirals with better clinical efficacy and less adverse events will be available to treat HCV infections worldwide.Keywords: danoprevir, ITMN-191, R7227, HCV NS3/4A inhibitor, HCV genotype